Evil, Excess and Transcendence - Martínez, Juan Pablo (Religions, 2023)
This article aims to overcome the prevailing philosophical views that understand evil from an ontological or metaphysical perspective through the reconciliation of being or God with the presence of evil in the world. In this sense, the phenomenological approach offers an adequate and renewed process to rethink the phenomenon of evil. To this end, I will show how the ontological treatment of evil as a deprivation of good corresponds neither to the way evil appears in experience nor to the recognition of the evidence of evil as a positive and effective reality that empirically rules and distorts relations within the world. This ontological consideration also fails to account for the transcendence of evil in its excessive condition, since this excess constitutes it as a phenomenon of radical exteriority to consciousness. Moreover, the overbearing and surprising presence of evil in the world demands from conscience a special spiritual penetration that does not justify evil, but rather exposes and condemns it. This can only be carried out in the disposition of the living to resist evil and to remain in the sphere of ethical difference, which consists of living in the good and for the good through the eradication of evil.